Novas Fronteiras no Oeste: Relação entre sociedade e natureza na microrregião de Ceres em Goiás (1940-2013) - Leal, Antonio Cezar [UNESP]; Ferreira, Rildo Mourão; Silva, Sandro Dutra E.; De Andrade Franco, José Luiz; Sayago, Doris Aleida Villamizar; Da Silva Barbalho, Maria Gonçalves; Tavares, Giovana Galvão; De Castro Peixoto, Josana (My University, 2015)
This paper aims to present a research project that is result of an ongoing partnership and interinstitutional cooperation of the faculty of the Graduate Program in Geography (Programas de Pós-Graduação em Geografia), of the Universidade Estadual Paulista Julio Mesquita Filho - Campus Presidente Prudente (PPGG/UNESP); Society, Technology and Environment (Sociedade, Tecnologia e Meio Ambiente) of the Centro Universitário de Anápolis (PPSTMA/UniEVANGÉLICA); and Sustainable Development (Desenvolvimento Sustentável) at the Universidade de Brasilia (CDS/UNB) in accordance with the objectives of the Programa Nacional de Cooperação Acadêmica (PROCAD), Notice No. 71/2013 Capes. The paper presents the main objectives and the methodological guidelines for the study of the micro region of Ceres, Goiás, through investigating environmental effects of the agricultural expansion during the 1940s. This research was performed concomitantly, with the thematic project approved by FAPESP, under the coordination of Prof. Dr. Antonio Thomaz Jr., and includes different methodological procedures, aimed at building interdisciplinary environmental knowledge, relying on multidisciplinary teams, with specific and integrated research at various levels (undergraduate, master, doctorate), study visits, research and teaching visits, the conducting of postdoctorates, organization of scientific events, joint publications, among others.
New frontiers in the west: The relationship between society and nature in the micro region of ceres in Goiás (1940-2013)
Keywords: Environment; Frontier; Micro region of Ceres; Natural resources